Olanzapine and risperidone plasma concentration therapeutic drug monitoring: A feasibility study. (August 2015) - Law, Suzanne; Gudbrandsen, Maria; Magill, Nicholas; Sweetman, Isabel; Rose, Diana; Landau, Sabine; Flanagan, Robert J; David, Anthony S; Patel, Maxine X
Background: This study aimed to develop a clinically acceptable method of therapeutic drug monitoring (TDM) for olanzapine and risperidone and to evaluate the feasibility of its implementation. Method: A non-randomised study of inpatients from five Mental Health Trusts was conducted, with a clinical interview at the time of TDM and a subsequent 6-week follow-up review of clinical notes. The TDM intervention comprised: (a) a venous blood sample taken 12 hours post-dose, 7–10 days after drug initiation, and (b) rapid results feedback, with interpretation algorithm guidance. Results: Thirty-two participants provided samples (19 prescribed olanzapine, 13 risperidone). Twenty-six participants remained on the target drug at study end, with seven experiencing a dose change, for whom only four of the TDM results were confirmed as having been checked. Mean dose increased for olanzapine (0.9 mg/day, range 0–10) and decreased for risperidone (-0.3 mg/day, range -4–3). Conclusion: TDM can be implemented as part of routine clinical practice for both drugs. However, the lack of robust supporting evidence for or against antipsychotic TDM has probably led to a lack of enthusiasm for and interest in the results. Nevertheless, the advent of less invasive measures and the targeting of patients who might be more likely to benefit may facilitate uptake.